Ethical and Methodological Considerations in Research with Asylum-Seeking and Refugee Youth in European Cities - Rik P. Huizinga; Peter Hopkins; Matthew C. Benwell; Mattias De Backer; Robin Finlay; Kathrin Hörschelmann; Elisabeth Kirndörfer; Ilse van Liempt (Social Sciences)
Research about the lived experiences of asylum-seeking and refugee youth can evoke powerful emotions for those involved. Young people who escaped perilous situations often bear strong emotions linked to their experiences of migration and displacement, as well as their encounters with disorientation, insecurity, isolation, discrimination and racism in unfamiliar contexts in the host society. Such emotions and emotionally charged places can be challenging to work with as researchers and require reflexive and situated methodological and ethical judgements. This paper investigates the emotional complexities of fieldwork with vulnerable young people by reflecting on (dis)comfort and discusses how to negotiate these issues with care and consideration. It draws from qualitative participatory and creative fieldwork experiences using story mapping, photovoice, walk-along and community theatre approaches in Amsterdam, Brussels, Leipzig and Newcastle-Upon-Tyne. It reports on a range of critical ethical and methodological issues that arose in our work that address meaningful relationships, reciprocity and trust, understanding the field, positionality and reflexivity, and challenges around the co-production of knowledge and leaving the field. Throughout, the paper flags various complex and, at times, ambiguous ethical and methodological issues that emerged throughout the research process and argues for research approaches that are sensitive to the contextual and multi-faceted nature of investigating young refugees and asylum seekers in European cities.